ANALISIS EFISIENSI USAHATANI PADI SAWAH LAHAN RAWA DI KABUPATEN CIAMIS (Suatu Kasus di Kecamatan Lakbok Kabupaten Ciamis) - T. Syaiful Azwar; Trisna Insan Noor; Ernah Ernah (Universitas Galuh Ciamis, 2019)
Rice is still an important commodity in agricultural policy in Indonesia because it is related to food security and rice self-sufficiency. The use of inefficient production factors will affect the level of farm productivity. The ability of farmers to manage and allocate production factors used will affect production and productivity, and will provide an overview of the level of efficiency achieved by farmers. The identification of the problem of this research are: 1) How is the performance of wetland rice farming in Lakbok Subdistrict? 2) Is there influence on the use of production factors together (simultaneously) and individually (partially) on the production of rice paddies in Lakbok Sub-district? 3) Is the average use of production factors on rice farming efficient or not? Test analysis using multiple regression analysis with a sample of 98 respondent farmers in Lakbok District, Ciamis Regency. Sampling is done by cluster sampling. The collected data were analyzed using quantitative descriptive approach and Production Factor Economic Efficiency Analysis. The results showed that: 1) The average yield of rice produced in Lakbok Subdistrict was 3,600 Kg / Ha MPD. While the total income for farmers in Lakbok District is Rp. 7,197,137.37 per hectare per planting season with RC ratio of 1.80 per planting season. 2) The amount of determination (R2) is 0.913. This can be interpreted that the independent variables (land area, seeds, fertilizers, pesticides, fungicides, insecticides and labor) can explain the dependent variable (rice production) of 91.1 percent, while the remainder is explained by other factors outside the derived model. While the value of the coefficient of determination obtained value of 0.958 means that the closeness of the relationship between the independent variable and the dependent variable is 95.8 percent. 3) The area of land, fungicides, insecticides and labor is greater than one, meaning that the combination of the use of production factors in the form of land area, fungicide, insecticide and labor in lowland rice farming has not been economic efficiency. While the value of economic efficiency for factors of seed and pesticide production shows a negative number, meaning that the use of production factors in rice farming is too much and will reduce the level of income earned.